2014
DOI: 10.1038/tpj.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen metabolism predicts drug concentrations and outcome in premenopausal patients with early breast cancer

Abstract: Tamoxifen is the standard-of-care treatment for estrogen receptor-positive premenopausal breast cancer. We examined tamoxifen metabolism via blood metabolite concentrations and germline variations of CYP3A5, CYP2C9, CYP2C19 and CYP2D6 in 587 premenopausal patients (Asians, Middle Eastern Arabs, Caucasian-UK; median age 39 years) and clinical outcome in 306 patients. N-desmethyltamoxifen (DM-Tam)/(Z)-endoxifen and CYP2D6 phenotype significantly correlated across ethnicities (R2: 53%, P<10−77). CYP2C19 and CYP2C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
225
5
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(264 citation statements)
references
References 59 publications
18
225
5
3
Order By: Relevance
“…In vitro and xenograft models have shown that breast cancer cell proliferation is endoxifen concentration dependent (16,17,20). Two large retrospective studies have shown a correlation between endoxifen level and disease-free survival in patients with early breast cancer treated with tamoxifen (18,19). Using quintile group analyses, both studies showed that endoxifen trough levels below approximately 15 nmol/L had worse outcome compared with those with higher levels in the adjuvant setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and xenograft models have shown that breast cancer cell proliferation is endoxifen concentration dependent (16,17,20). Two large retrospective studies have shown a correlation between endoxifen level and disease-free survival in patients with early breast cancer treated with tamoxifen (18,19). Using quintile group analyses, both studies showed that endoxifen trough levels below approximately 15 nmol/L had worse outcome compared with those with higher levels in the adjuvant setting.…”
Section: Introductionmentioning
confidence: 99%
“…There is now increasing evidence that systemic exposure to endoxifen is important for anticancer effect (16)(17)(18)(19)(20). In vitro and xenograft models have shown that breast cancer cell proliferation is endoxifen concentration dependent (16,17,20).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, endoxifen concentration may play a key role in modulating tamoxifen's clinical effectiveness (14). Lower concentrations of endoxifen have been associated with an increased risk of recurrent or new primary breast cancer (14,15). However, one prospective study found the opposite, suggesting that higher endoxifen concentrations promote recurrence (16).…”
mentioning
confidence: 99%
“…определили, что кон-центрация эндоксифена ниже 5,97 нг/мл коррелирует с увеличением рецидивов болезни [25], а P. Saladores и соавт. в своем исследовании установили, что уровень эндоксифена ниже 5,30 нг/мл влечет увеличение риска появления отсроченных рецидивов и смерти [34]. Одна-ко дальнейшее изучение необходимо.…”
Section: Discussionunclassified
“…были получены противоположные результаты: у носителей CYP2D6*4 наблюдалось снижение риска реци-дива болезни на фоне приема тамоксифена (relative risk = 0,28, 95% confi dence interval = 0,11-0,74, P=0,0089) и досто-верное увеличение DFS у гомозигот по CYP2D6*4 [29,30]. Также еще шесть исследований показывают достоверную связь между генотипом CYP2D6 и различными исходами лечения [17,[31][32][33][34][35][36] (табл. 1).…”
Section: Cyp2d6 и эффективность терапии тамоксифеномunclassified